POLBAN Chemical Engineering Community Empowerment at SMPN 15 Bandung Supporting Circular Economy - Lidya Risang Ayu; Dianty Rosirda Dewi Kurnia; Rispiandi; Dian Ratna Suminar; Rony Pasonang Sihombing (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Politeknik Negeri Bandung, 2026)
School waste management is a critical issue in Indonesia as it has not been prioritized effectively. Students generate approximately 25–100 grams of waste per day, potentially affecting environmental quality and public health. To address this issue, the Indonesian Ministry of Education and Culture introduced the Adiwiyata program in 2015 to encourage environmentally conscious schools. As part of the Tri Dharma of Higher Education, community service activities support knowledge transfer between universities and society to strengthen this program. This activity was conducted at SMPN 15 Bandung through demonstrations and counseling involving students and teachers, emphasizing circular economy principles and environmental empowerment. Ecoprint innovation introduced eco-friendly totebag coloring using natural plant pigments. Ecocraft activities promoted recycling through keychain production to increase material value. Additionally, ecofood innovation highlighted the utilization of watermelon rind, containing water, fiber, and bioactive compounds, as a value-added food product to reduce waste and improve economic potential.